Pemberian Pakan Alami Berbeda Terhadap Pertumbuhan dan Kecerahan Warna Ikan Zebra (Branchyndanio rerio) - Asep Rachmat Pratama (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2021)
This research aims to determine the best types of natural food for growth performance, survival rate and color brightness of zebrafish (Branchyndanio rerio). The research method of this research was using the experimental method with Completely Randomized Design (RAL) by using one factor of 4 treatment levels and 4 replications. The tratments were using pellet (control), Moina sp., Tubifex sp., and Chironomous sp. The fry size was around 1,6±1,03 cm and weight was 0,06±0,04 gr then reared in the aquarium by 15 liter of water and 15 fishes of stocking density each aquarium. The fish were reared for 60 days and feed was given as much as 10% of biomass weight, e times a day of feeding frequency. The results showed that the best treatment was Tubifex sp by giving absolute longevity for 0.58 cm, absolute weight growth for 0.14 gr, specific growth rate for 2.99% and fish survival for 98%, while the best color brightness by giving a Chironomous sp. with value 7,14±1,73. The conclusion is different types of natural diets significantly affects the growth performance, survival rate and color brightness of zebrafish (Branchyndanio rerio).